Nothing About Us Without Us: Reflections on the Protagonism of a Person with Low Vision in Human-Computer Interaction - Gouveia, Yndiana; Sacramento, Carolina; Nardi, Leonardo; Leal Ferreira, Simone Bacellar; Barros, Ygor Santos (Anais do Simpósio Brasileiro sobre Fatores Humanos em Sistemas Computacionais (IHC), 2024)
Digital inclusion and accessibility represent fundamental challenges in the field of Human-Computer Interaction (HCI), necessitating the development of interfaces that accommodate the specific needs of all users, including those with disabilities. Despite significant advancements in HCI, the representation of individuals with di-sabilities within higher education, scientific events, research, and the job market in Brazil remains notably limited. This article un-derscores the imperative for more inclusive research and practice, positing that individuals impacted by accessibility issues should be actively engaged in the design and evaluation processes. The primary objectives of this study are to explore how the needs of individuals with visual impairments, specifically those with low vision, are addressed within the Brazilian HCI community, and to advocate for the increased inclusion of people with disabilities in research roles. The study is structured in three stages: a bibli-ographic review of the Brazilian Symposium on Human Factors in Computing Systems (IHC), a narrative account of the personal experiences of the first author, who has low vision, and a series of reflections on the integration of these steps, with a focus on the participation of individuals with disabilities in HCI research and practice. The key findings suggest that the majority of studies tend to group blind and low vision users together, thereby neglecting their distinct needs. Furthermore, individuals with disabilities are frequently involved only in the later stages of research, often as participants rather than as co-authors or researchers. The article concludes with a call for the Brazilian HCI community to intensify its efforts to engage individuals with disabilities, ensuring their ac-tive participation from the inception to the completion of research projects.